Studies on the control of insect pests in vegetables (Okra, Tomato, and Onion) in Sudan with special reference to Neem-preparations - Ahmed, Mohamed Mudathir Mohamed; Justus Liebig University Giessen (My University, 2000)
Field trials were conducted for three years (1997-1999) to study the effectiveness of different neem formulations against the major insectpests complex and on yield of okra (Hibiscus esculentus), tomato (Lycopersicon escculentum), and onion (Allium cepa). Neem kernel powder was applied into the soil (NKPS), sprayed as water extract on the target plants (ANKE) or applied as water extractinto the soil (ANKES). The registered German formulated neem seed extract ( NeemAzal), includes Azadirachtin as main active principle,and, the Japanese trade product (Sumicidin) were also used for comparison. The experiments were conducted in the Shambat area of Khartoum in the Sudan. ANKE showed significant increase on yield of okra during the two seasons 1997 (162%), 1998 (52%), tomato 1998 (74%). An increase by28% of Okra 1999 was also obtained (nicht significant). Against the insect pests of okra, the product reduced the number of cotton aphids Aphis gossypii, white fly Bemisia tabaci (Genn.), thenumber of plants infested by the larvae of the spotted boll worm Earias vittella and the number of leaves damaged by the adults of the fleabeetle Podagrica puncticollis significantly. A reduction by 35% of the number of aphids on okra grown in the year 1999 was also recorded. Against the insect pest complex of tomato, ANKE reduced the number of the leaves damaged by the larvae of the leaf miner Liriomyzatrifolii significantly, while it reduced the number of aphids by 40%, and the number of white fly by 33% under the control. The product increased the weight of onion grown in the year 1999 by 15% over the control. A reduction by 21% and 26% of the number of cotton thrips T. tabaci on onion grown on the year 1998 and 1999 respectively, was alsorecorded. NeemAzal increased the yield of okra grown in the years 1997, 1998, and 1999 significantly. It succeeded also in the significant reduction of number of aphids on okra grown in the year 1998 and 1999, the number of plants infestedwith the larvae of spotted boll worm and the number of leaves damaged by the adults of flea beetle. It reduced the number of white fly notsignificantly by 58%. On tomato, NeemAzal increased the yield by 38% over the control (nich significant). It reduced the number of the leaves damaged by thelarvae of the leaf miner and white fly significantly, while it reduced the number of aphids only by 10% under the control. On onion, NeemAzal showed similar results as that of ANKE. NKPS increased the yield of okra grown in the year 1997 by 32% and the yield of tomato by 46%. On okra grown in the year 1998, itreduced the number of white flies and leaves damaged by the adults of flea beetle significantly, while it reduced the number of aphids onlyby 19%. On tomato, it reduced the number of white fly by 13% as compared with the control. ANKES reduced the number of white fly on okra grown in the year 1998 significantly. The results of NKPS and ANKES indicate a systemic movement of neem compounds from the root to the leaves. Sumicidin gave almost the same results as ANKE and NeemAzal in significant reduction of the number of tomato leaves damaged by thelarvae of the leaf miner. Against white fly on tomato, Sumicidin showed the same results as NeemAzal in significant reduction of the numberby 60%, but better as ANKE, which showed non-significant reduction by 40%. Against aphids on tomato, Sumicidin gave significant reduction of the number by 60%, while the reduction by ANKE and NeemAzal was notsignificant by 40% and 10% respectively. Although Sumicidin showed generally better results as the three-neem products (NeemAzal, ANKE and NKPS) against the target insectpest of tomato, all neem products gave yield higher than it did. On onion plants, Sumicidin showed better, but not significant effects on the weight and against cotton thrips than NeemAzal and ANKE. The results are summarized in Table 14, 15, and 16.A strong positive effect on the growth rate, vigor, plant height and number of leaves of okra and tomato plants treated with ANKE andNeemAzal were observed.
Keywords: insect pest; vegetable; neem-preparation; okra; tomato; onion; ddc:630